2012
DOI: 10.1210/en.2011-2120
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells Have Sex and So Should Journal Articles

Abstract: Males and females have the same immunological cells, proteins, and pathways in place to protect against the development of disease. The kinetics, magnitude, and skewing of the responses mounted against pathogens, allergens, toxins, or self-antigens, however, can differ dramatically between the sexes. Generally, females mount higher innate and adaptive immune responses than males, which can result in faster clearance of pathogens but also contributes to increased susceptibility to inflammatory and autoimmune di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
137
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 85 publications
(72 reference statements)
3
137
1
2
Order By: Relevance
“…Most importantly, associations of these biomarkers at baseline with sex, body measurements, and an oxidative balance score were consistent with previous findings from our group (42,45,46) and other groups (e.g., refs. [47][48][49], supporting the validity of our biomarker measurements. The baseline association of regular aspirin use with the cytokine z-score was opposite to what one might expect; however, this may have been the result of confounding by indication (i.e., subjects who took aspirin regularly likely were doing so for medical conditions associated with higher systemic inflammation), and thus should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 75%
“…Most importantly, associations of these biomarkers at baseline with sex, body measurements, and an oxidative balance score were consistent with previous findings from our group (42,45,46) and other groups (e.g., refs. [47][48][49], supporting the validity of our biomarker measurements. The baseline association of regular aspirin use with the cytokine z-score was opposite to what one might expect; however, this may have been the result of confounding by indication (i.e., subjects who took aspirin regularly likely were doing so for medical conditions associated with higher systemic inflammation), and thus should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 75%
“…How microbes perceive these sex-specific regulatory mediators may prove to be relative. Women are 30% more likely to develop irritable bowel disease than men (57,58). Studies have demonstrated estrogen to be contributive to GIT diseases, but the specific mechanisms associated with its action are largely understudied (57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Women are 30% more likely to develop irritable bowel disease than men (57,58). Studies have demonstrated estrogen to be contributive to GIT diseases, but the specific mechanisms associated with its action are largely understudied (57)(58)(59)(60)(61). Both females and males produce estrogen and estrogen receptors in GIT tissues, and learning more about these biological relationships could elucidate unexplored niches in disease (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, attendees also endorsed the editorial policies of several major scientific journals requiring the reporting of sex of the experimental material. [12][13][14][15] Dr. Londa Schiebinger emphasized how constructs of sex and gender influence all aspects of innovation in science, mathematics, and engineering as well as medicine. Through her efforts as Director of a joint program of Stanford University Center for Gendered Innovation, the European Union Research and Innovation, and the National Science Foundation, a website (www.genderedinnovations.eu) was developed to provide scientists and health care professionals easy access to definitions, methodologies, and examples of how viewing their work through a ''gender lens'' facilitates innovations.…”
Section: Designing Sex and Gender Analysis Into Research And Teachingmentioning
confidence: 99%